Reproducibility and Archaeological Practice in the Journal of Field Archaeology. - Farahani, Alan (Journal of Field Archaeology, 2024)
The Journal of Field Archaeology has implemented a new initiative for manuscript authors to reproduce their results using open-source code and data formats. Successful reproductions will be recognized with a badge on the manuscript and a "Reproducibility Statement." Reproducibility in this context refers to the consistent computational results using the same input data, methods, code, and conditions of analysis. This initiative aims to increase transparency, accessibility, and trust in archaeological research. It also facilitates data integration and enhances ethical practices in data analysis.